Impact of trade openness on economic growth, unemployment and environmental quality in OIC countries - Ali, Sajid (2021)
Today, the world is in favor of trade openness because open countries grow faster, are more productive, and have improved environmental quality than closed economies. The main objective of the thesis is to analyze the impact of trade openness on economic growth, unemployment, and environmental quality in OIC countries. Many studies argued that cross-sectional dependence exists among countries due to economic shocks and unobserved components as a result of trade openness (Arain et al., 2019; Dogan et al., 2020; Meo et al., 2020). The traditional econometric techniques give ambiguous outcomes in the presence of cross-sectional dependence and heterogeneity. So, in this study, a new technique ‘Dynamic Common Correlated Effects (DCCE)” proposed by Chudik & Pesaran (2015), is applied on panel data to deal with the above-mentioned issues. Moreover, for quantile-based analysis, another novel technique, “Quantile-on-Quantile (QQ)”, developed by Sim & Zhou (2015), is applied. Out of total 57, 49 OIC countries are selected for panel data analysis due to data availability. The first objective of the thesis explored the impact of trade openness on economic growth in OIC countries. The results of DCCE estimation state that there is a positive impact of trade openness on economic growth in the overall sample of OIC countries. Trade openness has a positive and significant relationship with economic growth in the case of higher-income OIC countries, whereas it decreases growth in the case of lower-income OIC countries. A quantile-based analysis indicates a positive association between trade openness and economic growth in the majority of OIC countries which support the trade-led growth hypothesis. The results tend to support the call for the continuation of trade openness policy for overall OIC countries and higher-income OIC countries. The second objective of the thesis has analyzed the impact of trade openness on unemployment in OIC countries. The DCCE estimation shows that trade openness has a negative and significant association with the unemployment rate in overall and lower-income OIC countries and a positive correlation with unemployment in higher-income OIC countries. A quantile based analysis indicates that trade openness increases unemployment in the majority of capital-abundant OIC countries and decreases unemployment in the majority of labor-abundant OIC countries. The results tend to support the call for the continuation of trade openness policy for overall OIC countries, lower-income OIC countries and labor-abundant OIC countries. The third objective is related to the impact of trade openness on environmental quality in OIC countries. Results of DCCE estimation identify a negative association of trade openness with CO2, N2O and CH4 emissions, while the positive relationship with the ecological footprint in overall OIC countries and higher-income OIC countries. On the other hand, trade openness has a positive association with all environmental indicators in lower- income OIC countries. A quantile-based analysis indicates a negative impact of trade openness on CO2 emissions and a positive impact on the ecological footprint in the majority of open OIC countries. It is recommended that if OIC countries continue with trade openness policies, energy sector reforms, and maintain sustainable use of biocapacity, then they will be able to combat environmental issues.